The Date of Invention of Babylonian Planetary Theory - Van der Waerden, В. L. (1968)
Introduction — 1. The Date of Lunar System A. — 2. System A for Jupiter and Mars — 3. Planetary Tables without Dates — 4. The Date of the Mars Table — 5. The Date of the Saturn Table — 6. Conclusions. — 7. Dareios I as a Patron of Science.